Estimates of genetic parameters of growth traits in Menz and Awassi x Menz crossbred sheep in Ethiopia - GIZAW, SOLOMON; JOSHI, B K (The Indian Journal of Animal Sciences, 2014)
A study on genetic evaluation of 3 678 Menz (M) lambs born to 85 sires and 3 021 Awassi x Menz (A x M) crossbred lambs of 28 sires, was conducted. Data collected during 1993-2000 at Amed Guya and Shena centers in the central highlands of Ethiopia, were used for the study. Traitli studied included birth weight (BWT), weaning weight (WWT). 6 month weight (6WT), yearling weight (12WT); average daily weight gains from birth to weaning (ADG1), birth to 6 months (ADG2), weaning to 6 months (ADG3) and 6 month to yearling age (ADG4). Heritability estimates ranged from 0.09±0.11 for ADG4to 0.33±0.11 for 12WT in M sheep, and 0.31±0.08 for ADG 1 to 0.78±0.23 for ADG2 in A x M crosses. The genetic correlations between growth traits ranged from 0.07±0.26 (betweenBWT and 6WT) to 0.96±0.18 (between 6WT and 12WT) for M sheep and from 0.35±0.24 (between WWT and 6WT) to 0.88±0.26 (between 6WT and 12WT) for A x M crosses. Repeatabilities ofBWT, WWT and ADG1 were of moderate magnitude. The results suggested that appreciable genetic improvement in marketing/slaughter weights could be achieved through selection on 6 WT or ADG2. A higher response is expected in A x M crosses and this would help in stabilizing the crossbreds through selective breeding.